Geometrical modeling of the process of weaving a wire cloth in weightlessness using the inertial unfolding of a dual pendulum - Kutsenko, Leonid; Semkiv, Oleg; Zapolskiy, Leonid; Shoman, Olga; Kalynovskyi, Andrii; Piksasov, Mykhailo; Adashevska, Irina; Shelihova, Inessa; Sydorenko, Olena (Eastern-European Journal of Enterprise Technologies, 2018)
We proposed a geometrical model for weaving a wire cloth using the oscillations of a system of two-link pendulums within an abstract plane and under conditions of weightlessness. It is expected to initiate oscillations through the application of pulses to each of the nodal elements of each of the pendulums, induced by two pulse jet engines. The pendulums are arranged in line on the platform, aligned with an abstract plane. The plane moves in the direction of its normal using the jet engines. Attachment points of the dual pendulums are selected so that when unfolded their last loads come into contact. Upon simultaneous initiation of oscillations of all pendulums and setting the platform in motion, we consider traces from the spatial displacements of the last loads of pendulums. It is assumed that wire that accepts the shape of the specified traces comes from the last loads and forms the zigzag-like elements of the mesh. In order to fix elements of the mesh, it is suggested that they should be point welded at the moments of contact between the last loads of the pendulums. A description of the inertial unfolding of dual pendulums is compiled using a Lagrange equation of the second kind, in which potential energy was not taken into consideration because of weightlessness. Reliability of the considered geometrical model for weaving a wire cloth was verified in a series of created animated videos that illustrated the process of formation of the elements of a wire cloth. Results might prove useful for designing large-sized structures in weightlessness, for example, antennas for ultralong waves.